1994
DOI: 10.1017/s0021932000021581
|View full text |Cite
|
Sign up to set email alerts
|

Assortative mating in a Spanish population: effects of social factors and cohabitation time

Abstract: Assortative mating for 22 anthropometric and body composition characteristics and social indicators was studied in a Spanish sample of 114 married couples. Significant spousal similarity was found for occupation, educational level and number of siblings. Sex-age adjusted spouse correlations were significant for stature, ileospinal height, total arm length, and biacromial breadth. Spouse correlations were not altered after allowance for socioeconomic effects. When couples were grouped according to marriage dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
2
4
0
1
Order By: Relevance
“…Zimmer (1981) investigated the social mobility-fertility hypothesis on a sample of women in Aberdeen, Scotland, and found that there was social homogamy among 47.4% of couples, 36% of wives and 16.6% of husbands were upwardly married. Significant occupational similarity between couples was observed in a Spanish sample by Sánchez-Andrés & Mesa (1994). The findings from this study indicate clear evidence of similarity between mates in social class: $39.9% of the spouses were from the same social class, 35.5% and 24.6% of females and males, respectively, were upwardly mobile by marriage, which is consistent with previous studies on the British national cohort (Mascie-Taylor, 1987).…”
Section: Discussionsupporting
confidence: 90%
“…Zimmer (1981) investigated the social mobility-fertility hypothesis on a sample of women in Aberdeen, Scotland, and found that there was social homogamy among 47.4% of couples, 36% of wives and 16.6% of husbands were upwardly married. Significant occupational similarity between couples was observed in a Spanish sample by Sánchez-Andrés & Mesa (1994). The findings from this study indicate clear evidence of similarity between mates in social class: $39.9% of the spouses were from the same social class, 35.5% and 24.6% of females and males, respectively, were upwardly mobile by marriage, which is consistent with previous studies on the British national cohort (Mascie-Taylor, 1987).…”
Section: Discussionsupporting
confidence: 90%
“…These regularities confirmed own research, where significantly higher magnitudes of the correlation among parents in the group of longer marriage stage were observed. However the results of our study are very close to the data of last new Polish and foreign investigations [2,16,24]. Thus relatively lower magnitudes of assortative mating of the analyzed traits that were noticed in this research, in the group of parents with short marriage stage allowed for summation that correlation coefficients presented are really a measure of selective mating among parents and that is why correction introduction to intra-families correlation coefficients was intentional.…”
Section: Resultssupporting
confidence: 88%
“…physical activity) are shared after the constitution of the couple. Sánchez-Andrés & Mesa (1994), in their study of a sample of Spanish spouses, detected some differences in marital resemblance for fatness variables depending on Assortative mating in the Basque Country the length of the marriage (i.e. time of common life).…”
Section: Discussionmentioning
confidence: 96%